Multimethodological analysis of hate speech patterns on social media: A study of Spanish-speaking incel communities - Renobell Santaren, Víctor; Jiménez Idrovo, Ítalo Vinicio; Solórzano Costales, Ángel Xavier; Fuentes de Frutos, Silvia (Revista de Ciencias Sociales, 2026)
The article analyses the patterns of hate speech present in Spanish-speaking incel communities on social media platforms such as Twitter and Instagram during 2024. The main objective is to develop and apply a mixed methodological approach, combining quantitative and qualitative techniques, to detect and characterise these misogynistic discourses and forms of symbolic violence. To this end, more than 20,000 posts and comments were collected and analysed using sentiment analysis, topic modelling, and discourse analysis, enabling the identification of the main narratives and references within these communities. The principal findings show that a multimethod approach is pertinent for the analysis of hate speech, revealing that patterns vary according to gender and, when referring to women, express emotions associated with social rejection, frustration, and alienation. Among its conclusions, the study highlights that integrating computational and qualitative methods is effective for disentangling the logic and patterns of hate speech in digital environments. Furthermore, the results indicate that the activity of incel communities not only reinforces misogynistic and exclusionary ideologies but also has harmful effects on both women and the members of these groups themselves, deepening participants’ isolation and radicalisation.